Bibliometric Analysis of The Effect of Discounts in E-Commerce on Increased Sales of Small and Medium Enterprise Products - Dwi Nugroho, Septian; Mujanah, Siti; Alif, Achmad Yanu (JEM17: Jurnal Ekonomi Manajemen, 2025)
As digital technology advances, internet shopping, or e-commerce, has grown in popularity and offers SMEs fantastic chances to boost sales. Offering discounts like price cuts, flash sales, and rebates is one tactic that's frequently employed to draw customers. In order to investigate trends and the effect of discount tactics on boosting sales of SME products, this study employs bibliometric analysis of Google Scholar data. According to the findings, there are 500 publications with four primary discussion groups: the usage of Shopee and other digital platforms, digital marketing tactics, the impact of promotions on customer behavior, and the function of promotions in aiding MSMEs during the pandemic. Keywords: E-commerce; Discounts; Digital promotion; MSMEs; Sales.